2011
DOI: 10.1088/0957-4484/22/11/115101
|View full text |Cite
|
Sign up to set email alerts
|

The effects of particle size, density and shape on margination of nanoparticles in microcirculation

Abstract: In the recent past, remarkable advances in nanotechnology have generated nanoparticles of different shapes and sizes, which have been shown to exhibit unique properties suitable for biomedical applications such as cancer therapy and imaging. Obviously, all nanoparticles are not made equal. This becomes evident when we consider their transport behavior under blood flow in microcirculation. In this work, we evaluated the effect of critical physical characteristics such as the particle shape, size and density on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
216
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(227 citation statements)
references
References 41 publications
8
216
3
Order By: Relevance
“…This so-called enhanced permeability and retention effect (8) further opens up the possibility of delivering chemotherapeutic drugs passively and more specifically to tumor sites, thereby limiting any damage to healthy tissues (9,10). A number of recent experimental (3,7,(11)(12)(13)(14)(15)(16)(17) and theoretical (18)(19)(20)(21)(22)(23) studies have suggested that particles of certain sizes and shapes have a higher margination propensity. This would facilitate the diffusion of these particles into tumor sites by allowing them to reach the leaky blood vessel walls and, ultimately, the tumors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This so-called enhanced permeability and retention effect (8) further opens up the possibility of delivering chemotherapeutic drugs passively and more specifically to tumor sites, thereby limiting any damage to healthy tissues (9,10). A number of recent experimental (3,7,(11)(12)(13)(14)(15)(16)(17) and theoretical (18)(19)(20)(21)(22)(23) studies have suggested that particles of certain sizes and shapes have a higher margination propensity. This would facilitate the diffusion of these particles into tumor sites by allowing them to reach the leaky blood vessel walls and, ultimately, the tumors.…”
Section: Introductionmentioning
confidence: 99%
“…A number of experimental (3,7,(11)(12)(13)(14)(15)(16)(17) and theoretical (19,(21)(22)(23) studies have explored the effect of varying particle size on the margination propensity of particles. Several studies suggested that larger particles marginate much more readily than smaller particles, and that there is an optimal particle size for margination (3,12,14,15,19,22,23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the matter of size effect on margination behavior, several studies have been reported on increasing the margination propensity by increasing the diameter of nanoparticles, [15,466] however, there is no agreement on the optimal size for margination. [467] It has been shown by several studies that nanoparticles of ≈50 nm in size achieve an optimal cellular uptake. [468] Such nanoparticles appear to have the highest internalization and modest exocytosis rates, [469] while nanoparticles with hydrodynamic sizes larger than 60 nm are poorly taken up by tumor cells.…”
Section: Passive Targetingmentioning
confidence: 99%
“…[179] However, if the particles are below a critical size (typically <100 nm), margination has been observed to increase again. [177,180] This behavior has been attributed to differences in the transportation mechanisms of particles with different size, which significantly affect the margination of particles. [178a,180] Moreover, blood composition is highly complex and blood cells can significantly affect the margination behavior of particles.…”
Section: Influence Of Fluidic Flowmentioning
confidence: 99%